Ictal and interictal electric source imaging in pre‐surgical evaluation: a prospective study. (8th June 2018) - Sharma, P.; Scherg, M.; Pinborg, L. H.; Fabricius, M.; Rubboli, G.; Pedersen, B.; Leffers, A.‐M.; Uldall, P.; Jespersen, B.; Brennum, J.; Henriksen, O. M.; Beniczky, S.
Abstract : Background and purpose: Accurate localization of the epileptic focus is essential for surgical treatment of patients with drug‐resistant epilepsy. Electric source imaging (ESI) is increasingly used in pre‐surgical evaluation. However, most previous studies have analysed interictal (II) discharges. Prospective studies comparing the feasibility and accuracy of II and ictal (IC) ESI are lacking. Methods: We prospectively analysed long‐term video‐electroencephalography recordings (LTM) of patients admitted for pre‐surgical evaluation. We performed ESI of II and IC signals using two methods, i.e. equivalent current dipole (ECD) and a distributed source model (DSM). LTM recordings employed the standard 25‐electrode array (including inferior temporal electrodes). An age‐matched template head model was used for source analysis. Results were compared with intracranial recordings, conventional neuroimaging methods [magnetic resonance imaging (MRI), positron emission tomography (PET), single‐photon emission computed tomography (SPECT)] and outcome at 1 year after surgery. Results: A total of 87 consecutive patients were analysed. ECD gave a significantly higher proportion of patients with localized focal abnormalities (94%) compared with MRI (70%), PET (66%) and SPECT (64%). Agreement between the ESI methods and intracranial recording was moderate to substantial ( k  =   0.56–0.79). A total of 54 patients were operated (47 patients more than 1 year ago) and 62% of them became seizure‐free. The localization accuracy of II‐ESI was 51% for DSM and 57% for ECD, and that for IC‐ESI was 51% for DSM and 62% for ECD. The differences between the ESI methods were not significant. Differences in localization accuracy between ESI and MRI (55%), PET (33%) and SPECT (40%) were not significant. Conclusions: The II‐ESI and IC‐ESI of LTM data have high feasibility and their localization accuracy is similar to that of conventional neuroimaging methods.